Conflict and Resolution of Waqf Disputes: Perspectives of Islamic Law and Positive Law in Indonesia - Razak, M. Akmal; Hamdan, Hamdan; Thalib, Hifni Syauqi; Kurniati, Kurniati (Abdurrauf Law and Sharia, 2025)
The potential for waqf in Indonesia is enormous, not only providing positive impacts in social and economic aspects, but also being vulnerable to conflict and waqf disputes. This is reinforced by the large number of uncertified waqf lands. This research is motivated by the low level of public understanding of the potential for conflict in waqf management in Indonesia. This study aims to analyze the forms of waqf conflicts in Indonesia and harmonize their resolution from the perspective of Islamic law and positive law. This research is a qualitative study using library methods conducted by collecting data from various literature such as books, journals, and relevant regulations related to waqf management and disputes. This study uses Islamic law and normative juridical approaches to address the focus of the study. The results show that the resolution of waqf conflicts through mediation and religious courts reflects an effort to harmonize the principles of Islamic justice with positive law mechanisms. This research emphasizes that synergy between Islamic law and national law is essential for creating effective, fair, and sustainable waqf dispute resolution. [Potensi wakaf di Indonesia sangat besar, tidak hanya memberikan dampak positif dalam aspek sosial dan ekonomi, namun juga rentan akan terjadinya konflik dan sengketa wakaf. Hal ini diperkuat dengan banyaknya tanah wakaf yang belum tersertifikasi. Penelitian ini dilatarbelakangi oleh rendahnya tingkat pemahaman masyarakat terhadap potensi konflik dalam pengelolaan wakaf di Indonesia. Penelitian ini bertujuan untuk menganalisis bentuk konflik wakaf di Indonesia serta harmonisasi penyelesaiannya dalam perspektif hukum Islam dan hukum positif. Penelitian ini merupakan penelitian kualitatif dengan metode kepustakaan yang dilakukan melalui pengumpulan data dari berbagai literatur seperti buku, jurnal serta regulasi yang relevan terkait dengan pengelolaan dan sengketa wakaf. Penelitian ini menggunakan pendekatan hukum Islam dan yuridis normatif untuk menjawab fokus kajian. Hasil penelitian menunjukkan bahwa penyelesaian konflik wakaf melalui mediasi dan peradilan agama mencerminkan upaya harmonisasi prinsip keadilan Islam dengan mekanisme hukum positif. Penelitian ini menegaskan bahwa sinergi antara hukum Islam dan hukum nasional penting untuk menciptakan penyelesaian sengketa wakaf yang efektif, adil, dan berkelanjutan.]